Simulation of Temperature Fields in Metals and Alloys Under the Energy Impact of High Pulse Power Density Ion Beams at Sub-Millisecond Duration; Energy Fluxes and Radiation Effects (EFRE-2024) - Ryabchikov A. I. Aleksandr Ilyich (2024, 2024)
Текстовый файл